Combined environmental and social exposures during pregnancy and associations with neonatal size and body composition: The Healthy Start study. Issue 2 (April 2019) - Martenies, Sheena E.; Allshouse, William B.; Starling, Anne P.; Ringham, Brandy M.; Glueck, Deborah H.; Adgate, John L.; Dabelea, Dana; Magzamen, Sheryl
Abstract : Background: Prenatal environmental and social exposures have been associated with decreased birth weight. However, the effects of combined exposures (CEs) in these domains are not fully understood. Here we assessed multi-domain exposures for participants in the Healthy Start study (Denver, CO) and tested associations with neonatal size and body composition. Methods: In separate linear regression models, we tested associations between neonatal outcomes and three indices for exposures. Two indices were developed to describe exposures to environmental hazards (ENV) and social determinants of health (SOC). A third index CEs in both domains (CE = ENV/10 × SOC/10). Index scores were assigned to mothers based on address at enrollment. Birth weight and length were measured at delivery, and weight-for-length z-scores were calculated using a reference distribution. Percent fat mass was obtained by air displacement plethysmography. Results: Complete data were available for 897 (64%) participants. Median (range) ENV, SOC, and CE values were 31.9 (7.1–63.2), 36.0 (2.8–75.0), and 10.9 (0.4–45.7), respectively. After adjusting for potential confounders, 10-point increases in SOC and CE were associated with 27.7 g (95% confidence interval [CI] = 12.4, 42.9 g) and 56.3 g (19.4 – 93.2 g) decreases in birth weight, respectively. SOC and CE were also associated with decreases in percent fat mass. Conclusions: CEs during pregnancy were associated with lower birth weight and percent fat mass. Evidence of a potential synergistic effect between ENV and SOC suggests a need to more fully consider neighborhood exposures when assessing neonatal outcomes. Abstract : Supplemental Digital Content is available in the text.